An empirical study on entrepreneurial bricolage behavior for sustainable enterprise performance of startups: Evidence from an emerging economy. Issue 1 (22nd July 2019) - Sivathanu, Brijesh; Pillai, Rajasshrie
Abstract : Purpose: This paper aims to study is to empirically investigate the role of entrepreneurial orientation (EOR), entrepreneurial bricolage (EBR), technology orientation (TOR), sustainability orientation (SOR) and Trust (TUR) in the sustainable enterprise performance (SEP) of tech startups in India. It uses a framework grounded in the EBR theory, upper echelon theory and resource-based view theory. Design/methodology/approach: A primary survey was conducted using a structured questionnaire amongst 285 sample respondents from 425 tech startups and the data were analyzed using the partial least squares-structural equation modeling technique. Findings: The findings suggest that EOR and TOR significantly influence SEP. SOR and TUR do not significantly affect the SEP. EBR plays a significant mediating role between TOR and EOR and SEP in the context of Indian technology-based startups. Research limitations/implications: This cross-sectional study has a geographic limitation as it was conducted in Mumbai, Bangalore and Pune and their suburbs. As this study was carried out in the context of tech startups in a developing country such as India, caution needs to be exercised while generalizing the findings of this study to other regions, countries and cultural contexts. Practical implications: This study highlights the significance of TOR and EOR in the long-term SEP to the budding entrepreneurs who have strong EOR and deploy EBR strategy to start their new business ventures. It also infers that few of the reasons for the failure of tech startups are because of the lack of attention to TUR and SOR. Originality/value: This study has a novel contribution as it empirically validates the role of multiple constructs such as EOR, TOR, TUR, SOR and EBR toward SEP in a resource-constrained startup environment in the context of a developing country such as India.